The Utilization of Physical Education Learning Media in Increasing The Active Learning Time of Elementary School Students - Sutarjo, Sutarjo; Hadiwinarto, Hadiwinarto (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to obtain a description of